Young Muslim generations and sadaqah through digital platforms: Do sadaqah literacy and religiosity matter? - Ahmad Santoso; Heri Sudarsono; Weni Hawariyuni (Review of Islamic Social Finance and Entrepreneurship, 2024)
Objective – This study aims to analyze the factors that influence young Muslims’ intention to use sadaqah payments through digital platforms.